NURSES KNOWLEDGE, ATTITUDE AND PRACTICES REGARDING ADVERSE DRUG REACTIONS AND PRESCRIBING CASCADES REPORTING IN TERTIARY CARE HOSPITALS, PESHAWAR - Zeb, Aurang; Afzal, Yasmeen; Khan, Mehreen; Shah, Abdullah; Jahan, Mehtab; Ahmed, Aftab; Banu, Safia (Annals of Allied Health Sciences, 2025)
Objective: To assess knowledge, attitude and practices (KAP) of nurses’ regarding adverse drug reactions and prescribing cascades reporting in tertiary care hospitals of Peshawar, Pakistan. Material & Methods: A cross-sectional study was conducted in tertiary care hospitals, Peshawar. The Rao soft online sample size calculator was used to determine the sample size of 224. A pre-designed, structured questionnaire was used to collect data via convenient sampling technique. SPSS version 20 was used for data analysis. Results: Majority of the participants (54.5%) had average knowledge. Only a few participants (21.4%), knew the term prescribing cascade. A considerable percentage of respondents (83.5%) agreed that ADRs reporting is their professional responsibility. Moreover, 52.2% of the respondents revealed that no ADR was reported by them during their practice and 78.1% reported that they haven’t filled in an ADR reporting form. Majority of the participants (65.2%) had poor practices regarding ADRs and prescribing cascades reporting. Nurses’ knowledge was significantly associated with age (P=0.009) and years of experience (P= 0.038). Conclusion: Nurses had average knowledge, ambivalent attitude and poor practices. It highlights a significant gap in both knowledge and practice related to ADRs and prescribing cascades reporting.